TINJAUAN KELAYAKAN EKONOMI RENCANA PEMBANGUNAN JALAN KRUENG MEUSAGOP – TEUPIN MANE DARI ASPEK PENGEMBANGAN WILAYAH DAN PRODUCER SURPLUS - Marwan Marwan; Sofyan M. Saleh; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
Economy of the community which will develop around the project sides that which on 7 sub-districts that are Simpang Mamplam, Pandrah, Jeunib, Peulimbang, Peudada, Jeumpa and Juli sub-district that are the area of superior commodity land on 7 sub-districts with surplus producer. The purpose of this research is to know how much benefit obtained from regional development and producer surplus of this road construction and and evaluate economic feasibility based on Benefit Cost Ratio (BCR). Scope of this research is scenario which covers plantation, agriculture, and farm sector that guided by plan of spatial pattern on Bireun District in 2012-2032 and this research was conducted in 7 sub-district which is in construction plan site of road Krueng Meusagop – Teupin Mane. Scenario results for 20 years since the road opened (2020-2040) economic benefits and advantages gained on the plantation area is Rp. 790.074.000.000,-, in the agriculture sector is Rp. 753.843.376.000,- and in farm sector is Rp. 455.340.741.000,-. Based on the economic evaluation of this road construction with a 20-year analysis period is meet the economic feasibility standards on the discount rate of 10% BCR value is 1,32 and NPV value is Rp. 89.228.473.000,-, discount rate of 12% BCR value is1,06 NPV value is Rp. 14.409.843.000,-.while on the discount rate 15% BCR value is 0,77.